2020
DOI: 10.1063/5.0013902
|View full text |Cite
|
Sign up to set email alerts
|

Suspended two-dimensional electron gases in In0.75Ga0.25As quantum wells

Abstract: We demonstrate that In 0:75 Ga 0:25 As quantum wells can be freely suspended without losing electrical quality when the epitaxial strainrelieving buffer layer is removed. In applied magnetic fields, non-dissipative behavior is observed in the conductivity, and a current induced breakdown of the quantum Hall effect shows a lower critical current in the suspended layers due to efficient thermal isolation compared to the non-suspended-control device. Beyond the critical current, background impurity scattering in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Due to the lack of heat removal directly through the substrate, overheating of the sample, and thus the QHE breakdown, are achieved at lower heating currents, which is consistent with the bootstraptype electron heating model [184]. Furthermore, it was found that beyond the critical current, background impurity scattering in the suspended 2D channel regions leads to stochastic, resonant-like features appearing in the conductivity before the onset of the Ohmic regime [179].…”
Section: Quantum Hall Effect In Suspended 2degsupporting
confidence: 73%
See 2 more Smart Citations
“…Due to the lack of heat removal directly through the substrate, overheating of the sample, and thus the QHE breakdown, are achieved at lower heating currents, which is consistent with the bootstraptype electron heating model [184]. Furthermore, it was found that beyond the critical current, background impurity scattering in the suspended 2D channel regions leads to stochastic, resonant-like features appearing in the conductivity before the onset of the Ohmic regime [179].…”
Section: Quantum Hall Effect In Suspended 2degsupporting
confidence: 73%
“…In addition to the AlGaAs/GaAs samples, suspended structures with a high mobility 2DEG in InGaAs/InAlAs heterostructures were created [178]. In these structures, vanishings of the longitudinal magnetoresistance and the corresponding quantization plateaus in the Hall resistance at temperatures below 1.6 K were found [179].…”
Section: Quantum Hall Effect In Suspended 2degmentioning
confidence: 99%
See 1 more Smart Citation
“…The above properties of the micro/nano electromechanical oscillators have been utilised in both simulations and experimentally in organic and inorganic structures [13][14][15][16][17][18][19][20][21]. Currently there is a growing interest in trying to observe many body localisation in solids state systems (MBL) [21].…”
Section: Introductionmentioning
confidence: 99%
“…The above properties of the micro/nano electromechanical oscillators have been utilised in both simulations and experimentally in organic and inorganic structures [13][14][15][16][17][18][19][20][21]. Currently there is a growing interest in trying to observe many body localisation in solids state systems (MBL) [21]. MBL can result in non-ergodic behaviour where disorder combined with electron-electron interactions can lead to regions of a device where the electrons states remain out of equilibrium with the rest of the device.…”
Section: Introductionmentioning
confidence: 99%